Investigations on the Spin States of Two Mononuclear Iron(II) Complexes Based on N-Donor Tridentate Schiff Base Ligands Derived from Pyridine-2,6-Dicarboxaldehyde - Yosef Bayeh; Nithin Suryadevara; Sören Schlittenhardt; Róbert Gyepes; Assefa Sergawie; Peter Hrobárik; Wolfgang Linert; Mario Ruben; Madhu Thomas (Inorganics, 2022)
Iron(II)-Schiff base complexes are a well-studied class of spin-crossover (SCO) active species due to their ability to interconvert between a paramagnetic high spin-state (HS, S = 2, 5T2) and a diamagnetic low spin-state (LS, S = 0, 1A1) by external stimuli under an appropriate ligand field. We have synthesized two mononuclear FeII complexes, viz., [Fe(L1)2](ClO4)2.CH3OH (1) and [Fe(L2)2](ClO4)2.2CH3CN (2), from two N6–coordinating tridentate Schiff bases derived from 2,6-bis[(benzylimino)methyl]pyridine. The complexes have been characterized by elemental analysis, electrospray ionization–mass spectrometry (ESI-MS), Fourier-transform infrared spectroscopy (FTIR), solution state nuclear magnetic resonance spectroscopy, 1H and 13C NMR (both theoretically and experimentally), single-crystal diffraction and magnetic susceptibility studies. The structural, spectroscopic and magnetic investigations revealed that 1 and 2 are with Fe–N6 distorted octahedral coordination geometry and remain locked in LS state throughout the measured temperature range from 5–350 K.